Pengukuran Kinerja Supply Chain Produk Pelumas dengan Pendekatan Supply Chain Operation Reference (SCOR) di Sebuah Perusahaan Multinasional - Vikaliana, Resista; Shafira, Asyifa Hana (Jurnal Ilmiah Giga, 2024)
PT XYZ is a multinational company from France that focuses on lubricant products. Problems at PT XYZ include overstocked items and damaged or defective product packaging during production, storage, and distribution. To compete in the Indonesian lubricant business market, it is necessary to analyze the supply chain performance using the SCOR model approach. The goal is to design supply chain performance indicators and propose improvements for low-performing areas. There are 12 existing KPIs and 8 additional KPIs from literature studies that have been adapted to the company's needs. KPI properties are compiled, and data is processed to determine the weights for each performance level with the help of Expert Choice. Data processing is carried out by calculating secondary data obtained for each KPI, except for KPI-8, KPI-13, KPI-14, and KPI-19, which do not have data requirements. Normalization is carried out for each KPI, and the total supply chain performance measurement for PT XYZ is 56.78, with an additional contribution value of 13.3. It can be concluded that around 70% of the maximum performance has been achieved, which falls into the "Good" category.